INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCES AT PTPN II KWALA BINGEI STATE, LANGKAT REGENCY - Purnomo, Candra; Daulay, Raihanah (Proceeding International Seminar of Islamic Studies, 2024)
Performance is How somebody expected can works And behave in accordance with task Which has in load to her. Performance in influence Lots among them Organizational Culture And Work Environment. Objective study This is For understand and analyze the influence of organizational culture and work environment to Employee Performance on PTPN II Kwala Bingei Stabat Regency Step up. Approach Which used in this research is a quantitative associative approach using Proportionate Stratified Random Sampling . Data collection methods use techniques interview And questionnaire. Technique analysis data use model regression linear multiple, classical assumption test, t test, f test, and coefficient of determination. Partial test results. There is the influence of organizational culture on performance, there is the influence of the work environment on performance. Simultaneous results show the influence of organizational culture and work environment on performance PTPN II Kwala Bingei Stabat Langkat Regency. The R Square value is 0.805, it shows 80.5 contribution variable independent to Employee Performance.